Методика прогнозирования исхода инфаркта миокарда левого желудочка задней локализации по данным клинического, биохимического и коагулографического анализов крови - Нужнова, С. В. (ХНУРЭ, 2008)
In the given work the questions of search a new decisions to task the prognostication a threat to development fatal end heart attack of myocardium in the left ventricle a back localization are considered. For prognostication end heart attack of myocardium in the left ventricle a back localization from data clinical one, biochemical and koagulagraphics blood tests diskrimintor allowing to promote quality the treatment-and-profylactic process arid were got, consequently, to lower lethality end heart attack a myocardium in the left ventricle a back localization.
Keywords: инфаркт миокарда; коагулографический анализ крови